The effect of pelvic tilt and cam on hip range of motion in young elite skiers and nonathletes - Swärd Aminoff, A.; Agnvall, C.; Todd, C.; Jónasson, P.; Sansone, M.; Thoreson, O.; Swärd, L.; Karlsson, J.; Baranto, A. (Open Access Journal of Sports Medicine, 2018)
Current knowledge of the effect of changes in posture and the way cam morphology of the hip joint may affect hip range of motion (ROM) is limited. Purpose: To determine the effect of changes in pelvic tilt (PT) on hip ROM and with/without the presence of cam. Study design: This was a cross-sectional study. Materials and methods: The hip ROM of 87 subjects (n=61 young elite skiers, n=26 nonathletes) was examined using a goniometer, in three different seated postures (flexed, neutral, and extended). The hips of the subjects were further subgrouped into cam and no-cam morphology, based on the magnetic resonance imaging findings in the hips. Results: There was a significant correlation between the hip ROM and the seated posture in both extended and flexed postures compared with the neutral posture. There was a significant decrease in internal hip rotation when the subjects sat with an extended posture with maximum anterior PT (p<0.0001). There was a significant increase in internal hip rotation when the subjects sat with a flexed posture with maximum posterior PT (p<0.001). External rotation was significantly decreased in an extended posture with maximum anterior PT (p<0.0001), but there was no difference in flexed posture with maximum posterior PT. The hips with cam morphology had reduced internal hip rotation in all three positions, but they responded to the changes in position in a similar manner to hips without cam morphology. Conclusion: Dynamic changes in PT significantly influence hip ROM in young people, independent of cam or no-cam morphology.